PENERAPAN STRATEGI PEMBELAJARAN KOLABORATIF TIPE PREDICT DISCUSS EXPLAIN OBSERVE DISCUSS EXPLAIN (PDEODE) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN DI KELAS XI SMA NEGERI 1 KAMPAR TIMUR - Fahm, Khairin Nisa; Azmi, Johni; Rery, Radjawali Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the improvement of student achievement by applying collaborative learning strategy type of predict discuss explain observe discuss explain (PDEODE) to improve student’s achievement of solubility equilibrium subject in class XI SMA Negeri 1 Kampar Timur. The study was an experiment with randomized control group pretest-posttest. The sample in this research is class XI MIA 1 as experiment class and class X1 MIA 2 as control class which is determined randomly after normality test anda homogeneity test. The experimental class is treated with the application of collaborative learning strategy type of predict discuss explain observe discuss explain (PDEODE) while the control class without the application of collaborative learning strategy type of predict discuss explain observe discuss explain (PDEODE). Data analysis for hypothesis testing is done using right-t test. Based on the results of data analysis obtained tct = 4,60 and ttable = 1,67 with= 0,05, dk = 56. tcount > ttable is 4,60 > 1,67 means the application of collaborative learning strategy type of predict discuss explain observe discuss explain (PDEODE) can improve studentachievement on hydrocarbon subject in class X SMA Negeri 1 XIII Koto Kampar. The percentage increase in learning achievement in the experimental class is 27,43%.Keywords : Collaborative learning strategy type of predict discuss explain observe discuss explain (PDEODE), learning achievement.